Learning and teaching of Islamic economics: conventional approach or Tawhidi methodology. Issue 2 (4th February 2021) - Azid, Toseef; Kayani, Zafar; Rawashdeh, Osamah Hussien; Shirazi, Nasim Shah
Abstract : Purpose: This paper aims to discuss the methodology of mainstream Islamic economics and also gives an alternative approach which is yet not very much taught in the different academic institutions, i.e. Tawhidi methodology. From the curriculum of the different academic institutions and also from the literature, it is observed that mainstream Islamic economics is the imitation of the conventional economics and mainly neoclassical economics. Maqasid-i-Shari'ah is not matching with the Tawhidi one. Design/methodology/approach: It is based on the self-observations of the authors where they taught during their academic career. Findings: This study found that the mainstream Islamic economics could not be able to solve the local and global issues because it is the replica of the conventional economics only there are some injunctions of Shari'ah. Research limitations/implications: This study gives the guideline to the student of Islamic economics that how they will be able to understand the methodology of Islamic economics and finance. Practical implications: It provides the guidance to the academicians and policymakers, especially those belonging to the Muslim countries. Social implications: It also provides the glimpses to the social scientist about the solutions of the social and economic issues at the local and global levels. Originality/value: It is an original effort.